Enhancing Statistical Thinking through Cooperative Mathematics Learning on Data Dispersion: A Classroom Action Research Study (2025) - Supratman; Rustam, Ahmad; Ramlan, Andi Mariani; Sirad, La Ode (Arden Jaya Publisher, 2025)
Statistical thinking is a fundamental competency in mathematics education, particularly in enabling students to interpret, analyze, and make decisions based on data. One essential topic that supports the development of statistical thinking is data dispersion, which includes measures such as range, variance, standard deviation, and interquartile range. However, many elementary students experience difficulties in understanding these concepts due to abstract explanations and teacher-centered instructional practices. This study aims to enhance students’ statistical thinking skills through the implementation of cooperative learning in mathematics instruction focusing on data dispersion. The research employed Classroom Action Research (CAR) conducted in 2025 with fourth-grade students at a public elementary school in Indonesia. The study was implemented across three cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through statistical thinking tests, observation sheets, and learning achievement assessments. The findings reveal a significant improvement in students’ statistical thinking abilities and learning outcomes across cycles, with classical mastery increasing from 61.1% in Cycle I to 83.3% in Cycle III. The results indicate that cooperative mathematics learning effectively facilitates conceptual understanding of data dispersion and fosters active engagement, reasoning, and collaboration among students. This study contributes to mathematics education research by providing empirical evidence on the role of cooperative learning in strengthening statistical thinking at the elementary level.